Anti-Diabetes Mellitus Potential Compounds Of Flavonoid Citrus Peel: A Review On Mechanism - Donny Risnanda Herdien; Cahaya Azzahra Rahmadhani; Septia Nurmala; Arry Yanuar (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2020)
Diabetes therapy with commonly used of anti-diabetes drugs (OAD) have unwanted side effects and the high price become problematic, so it is necessary to find or develop other safer, more effective, and inexpensive OAD alternatives. Based on in vitro and in vivo research models, flavonoids are proven to have efficacy in lowering blood glucose levels. In the citrus peel, flavonoid compounds are abundant. However their utilization is not optimal even though the mass production is very high. This study is to review current information regarding the effects of flavonoids on citrus peel in diabetes management and their molecular mechanisms. A literature review was conducted using the electronic databases of Scopus, ScienceDirect, and the American Chemical Society covering the most recent literature published from the years 2010 till present. Several keywords were combined to ensure all in vitro and in vivo studies were obtained. Key words used were “citrus peel”, “flavonoid”, “diabetes mellitus”, “mechanism”, and “blood glucose”.Based on the results of research that has been conducted by previous researchers, it was found that the flavonoids of citrus peel can improve glucose metabolism, hepatic enzyme activity, insulin signalling and lipogenesis regulation, repair damage to pancreatic islet cells and stimulate insulin secretion, and protect against complications of diabetes. Overall, citrus peel flavonoids as an antidiabetic can prevent an increase in blood sugar levels and reduce insulin resistance, the two hallmarks in diabetes melitus. Flavonoids play a role in enzyme inhibition, which is the main mechanism of medicine as well as inhibition at the level of gene expression and its antioxidant properties. Further research on the safety and efficacy of flavonoids is needed for the development of citrus fruit peel flavonoids as an alternative therapy for diabetes melitus.